Visual Poster Film Anime Akira Versi Tahun 2001 Dan Tahun 1989 Melalui Semiotika - Ramadhan, Mohammad Rezky; Ekawardhani, Yully Ambarsih (Fakultas Desain Universitas Komputer Indonesia, 2022)
Anime is a popular entertainment medium these days. Anime has several genres that describe the state of a particular society. One of them is the Anime film Akira which was released in 1988. This film has two variations of the poster which was released in 2001 and 1989. Both posters have different visuals. The difference lies in Kaneda's character which is shown differently from the angle of shooting, which in the 2001 poster Kaneda is shown from behind, while in the 1989 version it is shown from the front. Both Akira posters have elements related to the characteristics of Japanese society and culture, where there are several signs that are considered to have certain meanings. The selection of the method used in this study is the method of observation and descriptive explanation with semiotics from Roland Barthes, which is intended to find out the denotative and connotative meanings. Posters are studied by describing their visual elements, as well as being connected between meaning and related theories and presenting the results of the analysis of the explanation. the relationship between denotative and connotative meanings. This study was conducted to understand the representation of Japanese culture on Akira's posters.